“Effects of human disturbance on above-ground carbon stocks in north-west Amazonian Mauritia flexuosa peat swamp forests“ - Quinteros-Gómez, Yakov (2023)
“Mauritia flexuosa palm peat swamp forests concentrate important carbon reserves in the Amazon Basin, but are strongly affected by changes in land use. There is little information about their distribution pattern and carbon stocks in the Andean-Amazonian piedmonts. We studied four palm peat swamp forests of different types in two localities with different management, in the piedmont of the Alto Mayo Valley in San Martín Region, Peru. M. flexuosa showed an aggregated distribution (standardised Morisita index) and statistically significant differences in abundance and density between the four forests. The average above-ground carbon stocks of these palm forests were estimated at 61.5 Mg ha-1 (41.4–85.0 Mg ha-1 ), with M. flexuosa contributing 45.4 %. In the locality that was managed for conservation (Tingana), the above-ground carbon stocks were 77.9–85.0 Mg ha-1 , and thus approximately double those in the locality (Posic) with strong anthropic pressure (41.3–42.3 Mg ha-1 ).“